ANALISIS KARAKTERISTIK IBU DAN KONDISI KEHAMILAN YANG BERHUBUNGAN DENGAN KEJADIAN INTRA UTERINE FETAL DEATH (IUFD) - Faiza, Aulia Zulfiana Nur; Setyabudi, Muhamad Taufiqy; Ratnaningrum, Kanti (Al-Iqra Medical Journal : Jurnal Berkala Ilmiah Kedokteran, 2023)
Intra Uterine Fetal Death (IUFD) is still the cause of the increase in Neonate Death (AKN) and Baby Death (AKB) numbers in Indonesia. IUFD events can be caused by fetal factors, maternal factors, or placental factors. Several previous studies have analyzed the incidence factors of IUFD separately and still rarely studies that analyze several variations of IUFD risk factors reviewed from fetal and mother conditions simultaneously, therefore researchers want to know the relationship between parity, maternal age, pregnancy anemia, preeclampsia, and IUGR with the incidence of Intra Uterine Fetal Death (IUFD). Research is observational analytics with cross-sectional approaches and total sampling techniques. Data retrieval is conducted at Tugurejo Semarang Hospital. The research data was taken from secondary medical record data of pregnant women who experienced IUFDs from January 2018 - December 2021. Analysis of this research data using the Fisher Exact Test test. In this study, there was a link between parity, maternal age, pregnancy anemia, preeclampsia, and IUGR (p=0.033; p=0.037; p=0.016; p 0.010; p 0.000) with IUFD events.